Schaum's Physics Supplementary Problem 10-24: Moment of Inertia - Mitra-Kirtley, Sudipa (McGraw-Hill's AccessEngineering., 2013)
This video demonstrates the solution to a problem that is based on using the moment of inertia of a body into a conservation of energy example.